Preliminary study on internal carotid artery perfusion imaging and clinical application based on digital subtraction angiography - HU, Zhen; JIN, Wei; Dou YIN; Yu⁃lei DENG; LIU, Jun; Bin⁃yin LI (Zhongguo xian dai shen jing ji bing za zhi, 2022)
Background DSA is an irreplaceable diagnostic method for cerebral vascular disease. It is sensitive to intracranial macrovascular disease, but not to distal blood perfusion. In order to quantitatively assess the perfusion area of the feeding artery, this study is the first to propose an imaging method of the internal carotid artery (ICA) perfusion area relying on deconvolution algorithm and cross⁃correlation (CC) algorithm. Methods Four patients with cerebral vascular disease and 2 healthy subjects who underwent DSA examination in Luwan Branch of Ruijin Hospital Affiliated to Shanghai Jiaotong University School of Medicine from June 2020 to May 2021 were enrolled. The arterial input function (AIF) of the ICA was extracted, and a deconvolution algorithm was used to calculate the time to peak (Tmax) for each pixel. Then the CC algorithm was used to obtain the CC map related to the perfusion of the ICA at each pixel point of the whole brain. Area of interest (ROI) of AIF were randomly selected for 2 healthy subjects, calculated the root mean square error (RMSE) of the CC map for reliability analysis. The CC map was drawn for 4 patients with cerebral vascular disease for validity analysis. Results Reliability analysis showed that the RMSE values of Towne's and lateral views of the CC map and Tmax map of the left and right ICA in a healthy subject were 0.008±0.011, 0.022±0.002, 0.015±0.007, 0.004±0.008, and (0.108±0.181) s, (0.181±0.214) s, (0.301±0.230) s, (0.035±0.092) s; another healthy subject were 0.015±0.023, 0.007±0.011, 0.007±0.011, 0.005±0.012, and (0.172±0.275) s, (0.092±0.174) s, (0.087±0.156) s, (0.079±0.153) s. The averaged RMSE value of Tmax map was lower than the temporal resolution of DSA, indicating that the reliability of the CC map of the AIF value box in different ROIs of the ICA was high. Validity analysis showed that the CC map and Tmax map of the patient with acute ischemic stroke treated by intravenous thrombolysis bridging to mechanical thrombectomy can fully display the perfusion changes of the ICA after successful thrombectomy. Postoperative DSA in the patient with subacute ischemic stroke after endovascular therapy showed recanalization of the occluded artery, while the CC map showed no significant change in the perfusion of the ICA. The DSA of the patient with middle cerebral artery (MCA) stenosis without related ischemic events showed severe MCA stenosis, but the CC map showed that the ICA was well perfused, and no endovascular treatment was required. The DSA of the patient with acute ischemic stroke without MCA stenosis showed no MCA stenosis, but only sparse ICA⁃related perfusion was seen on the CC map. Conclusions The CC map and Tmax map based on DSA images have good reliability in different ROIs of AIF. The CC map can provide quantitative information on the perfusion area of the feeding arteries, which is helpful for accurate diagnosis and appropriate treatment decisions.